Where the response to migration begins: Zygmunt Bauman’s considerations about exile and migration - Álvarez-Álvarez, Elena (SOCIAL REVIEW. International Social Sciences Review / Revista Internacional de Ciencias Sociales, 2021)
Migration is one of the main problems in the modern world, one which is globally generated, but left to the individual’s or small community’s initiative. My proposal is that any solution – including the people’s exigence to governments – must start with ethics, particularly by exchanging attitudes of prejudice and indifference toward migrants for attitudes of responsibility toward the other in need, and solidarity. I discuss some texts from Zygmunt Bauman because he has been one of the most renowned analysts of our society, and he himself was an exile.